Answer:
• The real number a = -5
,
• The real number b = 0
Step-by-step explanation:
Given the expression:
![\mleft(-4-3i\mright)+(-1+3i)](https://img.qammunity.org/2023/formulas/mathematics/college/ik75ruym5rl7tk5ykcca8oc9viogc01bwt.png)
First, remove the brackets:
![=-4-3i-1+3i](https://img.qammunity.org/2023/formulas/mathematics/college/3upecvpqtsttnmxih8hj7q5eq7yzoyc4r8.png)
Next, bring the like terms together:
![\begin{gathered} =-4-1-3i+3i \\ =-5+0i \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ag6gqgf9kpmiztoif24800rbep0nqfyjld.png)
The result in the form a+bi is:
![-5+0i](https://img.qammunity.org/2023/formulas/mathematics/college/r5jiqu5a15ippwwfe7asyb92eb79yeqozn.png)
Thus:
• The real number a = -5
,
• The real number b = 0